Peningkatan Potensi Desa Berbasis Indeks Desa Membangun di Desa Sidomukti melalui KKN-T Kolaboratif Universitas Bojonegoro - Reza Anggapratama; Bima Kusumanjaya; Ranti Safitri (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2023)
The Bojonegoro University Collaborative Thematic KKN activity carried out in Sidomukti Village, Kasiman District, Bojonegoro Regency, is a community service activity which aims to increase the village development index so that Sidomukti Village can become an independent village through community empowerment. All work programs are prepared based on the Developing Village Index, which is divided into environmental, social and economic dimensions. The method for implementing this activity is by observing the conditions of the village and community, and then the results of these observations are discussed and coordinated with the community so that a work program is obtained, including (1) Procurement of trash bins, (2) Counseling for MSMEs on Digital Marketing, (3) Provision of Reading Parks, (4) Teaching in Elementary Schools, (5) Socialization of the Use of BPJS, and (6) Renovation of Kamling Posts. The community fully supported this work program and produced results as planned. The results of KKN's activities are that people have thrown away rubbish in the places that have been made, children have liked reading books, people have become aware of the importance of BPJS, and MSMEs have understood digital marketing. This KKN activity also pays attention to aspects of the Village SDGs so that even though the activity has ended, it still has a sustainable impact.